Preparation and characterization of mango (Mangifera Indica Casia) peel pectin - Yu, Aileen N.; Del Valle, Mercedita (1978.)
Mango peel which constitutes about 20 to 25% of mango processing waste was used as a source for the preparation of pectin. Rare-ripe and fully ripe mangoes (Mangifera indica casia) commonly called the Baluno variety were used. The extraction of pectin was carried out according to the method described by Kertesz (1951). Extraction was done at 80°C using acidified water, followed by precipitation with 95% ethanol. Average yields of 14.68% and 10.87% pectin were obtained from rare-tipe and fully ripe mango peels respectively. The methoxyl content of rare-ripe peel pectin was 8.44% while fully ripe peel pectin contained 8.25% methoxyl. Equivalent weights were determined as 808.52 and 807.68 g-eq. wt. for rare-ripe and fully ripe peels respectively. Jelly grade of the peel pectin was estimated to be a value close to 150.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mango